NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA TRADISI YANG DILAKUKAN SAAT USIA KEHAMILAN PADA MASYARAKAT DESA WONOSARI BENGKALIS - Susanti, Eti; Suseno, Suseno; Jarir, Jarir (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Pregnancy traditions that develop in the Wonosari Village community, Bengkalis District, Riau Province, are a form of local wisdom that contains Islamic religious education values. These traditions are not merely expressions of culture or customs passed down from generation to generation, but also function as a means of internalizing Islamic teachings into people's lives. This study aims to identify and analyze the values of Islamic education contained in social practices during pregnancy, such as four-monthly religious studies, reading of the letters Maryam and Yusuf by pregnant women, and thanksgiving and alms activities. The method used is a descriptive qualitative approach with data collection techniques through observation, light interviews with community leaders, and literature studies. The results of the study indicate that these traditions contain dimensions of monotheism, worship, morals, and Islamic brotherhood education that are implemented contextually and applicatively. These values also strengthen the role of the family and community as agents of non-formal education that instill Islamic teachings naturally since the prenatal period. Therefore, the preservation of pregnancy traditions based on Islamic teachings needs to be continuously encouraged as part of efforts to build a sustainable cultural-based Islamic education system.